Al- Burz, a Mountain Range in Iran and its Relation with Brahuis - Razzaq, waheed (Al-Burz, 2009)
Two things inspired me to write something about, AI-Burz, the name of a mountain range in Iran first long ago when I had been listening and reading about AI Burz and its relation with Brahui, and secondly, the name proposed for the newly research journal of Brahui department, University of Balochistan by Dr Hameed Shahwani the former chairman Brahui Department and present Dean of the Faculty of languages and Literature. To participate in the ceremonies of the second death anniversary of Allama Ayatullah Khomeini and to participate in the international Conference on Palestine in Tehran, Iran I along with eminent scholars Prof. Abdullah jan Jamaldini, Prof. Muhammad Khan Raisani, (The then Vice Chancellor of the University of Balochistan) Prof. Nadir Qambrani, Agha Mir Naseer Khan Ahmedzai visited Iran in May, 1991, I witnessed this famous “Alburz” mountain first time, from windows of my room in hotel Estighlal, Tehran. Like Chiltan in Quetta we all enjoyed the scene and discussed it time and again, Returning back to Pakistan I again saw the highest peak of Al-Burz, namely “Koh-i-Damawand” from my window seat in the plane and aksed my senior accompanies Prof. Jamaldini and Nadir Qambrani to see it. Meanwhile, Prof. Jamaldini during the flight up to Karachi fascinatingly recounted the history of “Koh Damawand” and its relations with famous Iranian ancient characters. Here it is a precise introduction of the mountain for the readers of the journal namely “Al-Burz”.